Experience of management of abdominal cysts - Vaze, Dhananjay; Jhadav, Pranav; M., Rajesh; Hegde, Adarsh; Raut, Sanjay; Shimpi, Ashlesha; Bhagwat, Aniruddha (International Surgery Journal, 2020)
Benign intra-abdominal cystic masses in children are rare and they have diverse etiopathogenesis, clinical presentation. The present study highlights the experience in the management of benign intra-abdominal cysts pertaining to the diverse etiologies associated with these lesions. The medical records of our hospital between November 2016 to November 2019 were retrospectively reviewed. Patients with cystic abdominal masses were studied with respect to less different clinical presentations, localization of masses, diagnostic tests, surgical aapproaches, histopathological examinations and outcome. Out of the 55 cases, most common lesion was a choledochal cyst. Miscellaneous diagnosis includes an omental cyst, urachal cyst and a pedunculated bile duct cyst. All the cystic lesions of the abdomen need to be considered as close differentials in clinical practice due to the common presentations and similar symptoms produced by these lesions. All the lesions were managed by exploratory laparotomy except two ovarian cysts which were managed with laparoscopic approach.